Dietary microbes and functional dyspepsia: modulating the gut microecology for therapeutic benefit - Qi Huang; Fei You; Fengxia Liang; Chaoyang Ma (Frontiers in Nutrition)
The pathogenesis of functional dyspepsia (FD) is closely associated with intestinal microecological alterations. Dietary microorganisms, capable of modulating gut microecology and thereby influencing gastrointestinal function, are being explored as a promising therapeutic strategy against FD. However, the precise mechanisms underlying how dietary microbes exert beneficial effects through microecological modulation, along with therapeutic protocols, remain incompletely defined. This article systematically reviews the manifestations of intestinal microecological imbalance in FD and its proposed pathogenic mechanisms. We critically examine the role of dietary microorganisms in mitigating FD through microecological regulation, addressing their potential mechanisms of action and clinical impacts. Integrating advances in emerging diagnostic technologies, we further discuss feasible approaches and potential targets for personalized FD management. Current controversies and challenges within this research domain are analyzed, alongside perspectives for translating these findings into clinical practice. Collectively, this review aims to provide a comprehensive theoretical framework and inspire insights for both in-depth research and improved therapeutic strategies for FD.